Model kanonizacije evropskih kulturnih svetnikov - Dović, Marijan (Primerjalna književnost, 2012)
This article presents a new framework for studying the canonization of the European "cultural saints". The framework includes the study of canonical "potentials" of the candidate ("vitae"), the canonization in the narrow sense, consisting of foundational and confirmative features ("inventio") as well as those that warrant the perpetual reproduction of canonicity ("cultus"), and the broader social implications of the process ("virtutes").
Keywords: evropska književnost; nacionalne književnosti; kanonizacija; literarni kanon; kulturni spomin; kulturni svetniki; nacionalna identiteta; nacionalni pesniki